2014
DOI: 10.1021/jp501133w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Trajectory Entropy for Continuous Stochastic Processes at Equilibrium

Abstract: The analytical expression for the trajectory entropy of the overdamped Langevin equation is derived via two approaches. The first route goes through the Fokker−Planck equation that governs the propagation of the conditional probability density, while the second method goes through the path integral of the Onsager− Machlup action. The agreement of these two approaches in the continuum limit underscores the equivalence between the partial differential equation and the path integral formulations for stochastic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The PMF profiles also predicted that both the α8-closed and the α8-open states should coexist in room-temperature solution and that the α8-closed state would be more populated, in agreement with the single-molecule results . In principle, it is possible to infer the structural and kinetic elements by deep analyses of single-molecule traces and compare the results with the computational PMF obtained here; work along this line is currently underway.…”
Section: Resultssupporting
confidence: 76%
“…The PMF profiles also predicted that both the α8-closed and the α8-open states should coexist in room-temperature solution and that the α8-closed state would be more populated, in agreement with the single-molecule results . In principle, it is possible to infer the structural and kinetic elements by deep analyses of single-molecule traces and compare the results with the computational PMF obtained here; work along this line is currently underway.…”
Section: Resultssupporting
confidence: 76%
“…In principle, the additional information for improving the inference could also be physical models. One sees such precedents in singlemolecule time series analysis: the distance and time resolutions in continuous single-molecule Förster resonance energy transfer time series analysis are drastically improved from data-driven inference (71,72) to analysis based on Langevin dynamics (73)(74)(75)(76), and the time resolution in singlemolecule on/off intensity instances could be further refined from kinetics model-free analysis (77)(78)(79) to that based on hidden Markov modeling (80).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several works have suggested that statistical learning from continuous experimental signals is not intractable. They range from direct analysis on the signal level to statistical learning of the dynamics parameter guided by a physical model and to the more abstract theoretical objects. , It is hoped that with these and many forthcoming new developments the pace of new discoveries will be greatly accelerated.…”
Section: Discussionmentioning
confidence: 99%